Conference runs to seed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Papers from the 6th International Workshop on Seeds held in Mexico in January 1999 describing the current status of seed biology.Seed Biology: Advances and ApplicationsEdited by M J Black, King s College, University of London, UK, K J Bradford,...